Community-Based Tourism in the Sustainability Tourism of Open Pit Nam Salu in East Belitung Regency - Alia Bihrajihant Raya; Siti Fatonah; Vinki Adindani Qurayma; Nanang Wahyudin; Roso Witjaksono (AIBPM Publisher, 2025)
Community-based tourism (CBT) provides a framework for sustainable tourism by ensuring that development benefits the community while preserving cultural and natural resources. This study aimed to analyze the sustainability of the Open Pit Nam Salu Geosite in East Belitung by applying a CBT framework and examining the direct and indirect effects of group roles, natural capital, and community motivation. The research was conducted in Senyubuk Village using a quantitative approach with 87 respondents selected through cluster sampling. Data were analyzed using SEM-PLS. Results show that group roles had the strongest direct effect on tourism sustainability (? = 0.306, p = 0.009), followed by community motivation (? = 0.269, p = 0.014). Natural capital did not significantly influence sustainability directly, but exerted an indirect effect through community motivation (? = 0.141, p = 0.053). Group roles also contributed indirectly through natural capital and community motivation (? = 0.098, p = 0.060). These findings indicate that CBT at Open Pit Nam Salu has not yet been implemented optimally, as participation remains limited. Strengthening BAPOPNAS’s task roles, enhancing community involvement, and transforming natural capital into motivational drivers are key strategies to ensure sustainable post-mining tourism development